EFEKTIVITAS MEDIA WEBSITE INTERAKTIF BERBASIS PBL TERHADAP KEMAMPUAN BERPIKIR TINGKAT TINGGI PESERTA DIDIK SEKOLAH DASAR - Heru Windarto; Agus Wardhono; Mu’jizatin Fadiana; Heny Sulistyaningrum (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to measure the effectiveness of an interactive website based on problem-based learning (PBL) in improving students' higher-order thinking skills. The method used is quantitative with a quasi-experimental design, with a single group pretest-posttest design with a sample of 27 children in class VB at UPT SD Negeri Manjung. Data collection techniques were conducted through written tests, and the data collection process was carried out using instruments in accordance with the indicators of the higher-order thinking variable. The data analysis technique used was a normality test and a t-test using SPSS 25 software. Effectiveness was calculated using normalised N-Gain analysis. The results showed that (1) the paired t-test analysis of higher-order thinking skills data yielded a sig value (2-tailed) of 0.000 with α = 0.05, indicating that the treatment had a significant effect on students' higher-order thinking skills. (2) The average N-Gain score for higher-order thinking skills was 0.58, which falls into the ‘Moderate’ category with the criterion ‘sufficiently effective’. Overall, this study concludes that the use of interactive PBL-based website media can improve the higher-order thinking skills of primary school students.